Rancang Bangun Sistem Informasi Pengolahan Data Pemilih Pada Sekretariat Komisi Pemilihan Umum Kabupaten Purwakarta (KPU) Pada Tingkat Panitia Pemilihan Kecamatan (PPK) - Prio Kustanto; Halimil Fathi (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2020)
In the Simultaneous General Election in the Election of Regent, Deputy Regent, Legislative, President, Vice President as election organizer, namely the General Election Commission (KPU) of Purwakarta Regency. Assisted by the District Election Committee (PPK), the Voting Committee (PPS) formed by the Purwakarta Regency KPU to carry out the General Election at the sub-district level and at the village level. Updating voter data in managing Election Data at General Election organizers that do not yet have voter data managed into a database, especially at the sub-district, village / family level, so that the District Election Committee (PPK) has difficulty managing Voter Data. The method used in designing the information system for processing voter data based on the Desktop Application uses Visual basic 6.0, Crystal report 8.5 and DBMS MySQL, which has a real database for managing voter data that can provide appropriate information in the implementation of the General Election. The method used in this research is Waterfall.The purpose of this research is to build a system that can process desktop-based voter data management so as to produce a report on recapitulation of voter data per district, recapitulation of voter data based on Village and based on TPS, double data processing, and recapitulation of deletion data based on criteria.